A Study on Gender Differences in Morality and Ethics: From the Perspective of Feminist Therapy - LEE, Ju–yeon (Asian-Pacific Journal of Social Quality, 2015)
Feminist therapy, based on feminist philosophy, has the aim of supporting and strengthening the powers of social minority groups, including women, and bringing change to society through these efforts. Its basic principle is that of equality, seeking freedom from any prejudice or oppression coming from gender differences. Through the analysis of a commercial entitled “Show,” by Korea Telecom, this study discusses how women, and especially women’s sense of ethics, are viewed in society. The commercial has been analyzed according to ethical theories, and a tentative conclusion has been reached: Women’s ethics is more relationshiporiented and caring than that of men, and it is the product of experiences, and learned through a system. Men and women are not innately different in terms of ethics, but rather the difference is something experienced, learned, and encouraged, and people acquire this difference in the course of interacting with others in order to survive. Taking this into consideration, the current study proposes and discusses a new method of dealing with ethics in feminist therapy: The fact that difference exists should be acknowledged, and an effort should be made to ‘show’ various effects of this difference.